An Empirical Investigation of Leadership and Human Resources Capacities as Key Actors in the Implementation of Smart Education - Xuhui Wang; Jonela Wilson; Wenjing Li (MDPI AG, 2021)
Due to the novelty of the smart education phenomenon, a quantitative investigation of the variables that will influence the implementation of 'smart education' was needed. Therefore, based on a probability simple random survey of 349 Grenadian employees from tertiary institutions in the education industry, the influence of leadership and human resource capacities on smart education were investigated. Results produced from SPSS analysis software and Smart PLS revealed that leadership and human resources capacities have sufficient confidence to have a significant influence on smart education, producing a positive association with 'smart education.' However, this relationship is positively moderated by additional investments, such as infrastructural innovation. These findings enrich the current literature on smart education (SE) by increasing knowledge of the phenomenon through the lenses of the Actor-Network Theory and Technology Adoption Model. Accordingly, policymakers should bear these findings in mind when developing holistic strategies to guide SE's successful enactment.